O acesso dos usuários transfronteiriços paraguaios aos serviços públicos de saúde no Brasil - Martínez, Virginia Ruiz de Martín Esteban Martínez (2020)
The study of access to Brazilian public health services by cross-border users is relevant to identify barriers and elements that help to further improve access and reduce social and health inequities. The general objective of the study was to understand how occurs the access of Paraguayan cross-border users to public health services in Brazil. It is a qualitative research, descriptive and exploratory, using, for data analysis, the theoretical framework of the model of access to health by Aday and Andersen (1974) and, for data organization, the WebQDA software was used. For the treatment of the material, the content analysis technique of thematic analysis by Bardin (2011). 13 semi-structured interviews were carried out between July and September 2019. The results point to the continuous demand for health services with the predominance of the use of urgencies compared to other levels of assistance. The type of use is curative, according to the utilitarian concept. The reason for access is the precarious and insufficient infrastructure of the system on the Paraguayan side and, the proximity and the free services in Brazil. Users perceive good technical quality of services and good treatment in attendance, however, they are all conditioned to the possession of the Sistema Único de Saúde (SUS) card. The access barriers identified are the documentation required from the high bureaucracy, the lack of information on access, the lack of knowledge of the right to health, the perception of discrimination, the excessive waiting time and the discontinuity in the attendance due to political changes and the random criteria of the health teams. The communication difficulty is mitigated by the use of Portunhol. Those who do not have the documentation use others ways or subterfuge. A solidarity network existing in the border region formed by family members, acquaintances and the technical role of Casa do Migrante is perceived. Among the conclusions, it stands out that the Paraguayan cross-border health access in the municipality is restricted to emergencies and urgencies' situations, without the university acting as an instrument of international citizenship. Users and health teams need to be well informed about health rights, guaranteeing the access. The offer by the system of accurate, accessible and available information, in Spanish on the functioning and organization of health services and the qualification of health teams on notions of interculturality are recommended to overcome access barriers. Intersectoriality is considered a key strategy to reduce health inequalities, and supranational understanding is needed for the development of regional integration health actions, based cooperation agreements between twin cities' municipalities, involving all borders’ actors, with transnational approaches that complement traditional local health systems.